2016
DOI: 10.2337/dc16-1579
|View full text |Cite
|
Sign up to set email alerts
|

Among Low-Income Respondents With Diabetes, High-Deductible Versus No-Deductible Insurance Sharply Reduces Medical Service Use

Abstract: OBJECTIVE To contrast the effect of private insurance and deductibles (by size) on medical service use, health status, and medical debt for adult respondents with diabetes with low and high incomes. RESEARCH DESIGN AND METHODS Using the 2011–2013 Medical Expenditure Panel Survey, bivariate and regression analyses were conducted to compare demographic characteristics, medical service use, diabetes care, and health status among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…Although rates of hyperglycemic emergencies may be higher among uninsured patients owing to poor access to medical care, healthy food, and housing, 16 , 34 many people with employer-sponsored private health plans have high deductibles and out-of-pocket cost-sharing expenses, 35 which may be associated with financial distress 36 and greater likelihood of forgoing necessary medical care. 37 Young patients may be particularly susceptible to financial instability and underinsurance, 34 , 38 which may be associated with poor glycemic control, 21 , 34 , 39 , 40 inadequate ambulatory care, and ultimately, higher rates of hyperglycemic crises, like those observed in our study. Thus, multidisciplinary teams should anticipate these barriers to care, develop care plans that are affordable and accessible, and help patients navigate available support programs.…”
Section: Discussionsupporting
confidence: 59%
“…Although rates of hyperglycemic emergencies may be higher among uninsured patients owing to poor access to medical care, healthy food, and housing, 16 , 34 many people with employer-sponsored private health plans have high deductibles and out-of-pocket cost-sharing expenses, 35 which may be associated with financial distress 36 and greater likelihood of forgoing necessary medical care. 37 Young patients may be particularly susceptible to financial instability and underinsurance, 34 , 38 which may be associated with poor glycemic control, 21 , 34 , 39 , 40 inadequate ambulatory care, and ultimately, higher rates of hyperglycemic crises, like those observed in our study. Thus, multidisciplinary teams should anticipate these barriers to care, develop care plans that are affordable and accessible, and help patients navigate available support programs.…”
Section: Discussionsupporting
confidence: 59%
“…Health insurance coverage needs to be affordable to improve access to health care and, consequently, reduce diabetesrelated complications. A recent national study showed that lower-income adults with diabetes who had high-deductible insurance plans had significantly lower service use for primary care and specialty visits than lower-income adults with no deductible or a low deductible (16). In the current study, the percentage of income spent on family medical costs significantly decreased over the study period among those with the lowest income, regardless of age; family medical costs were out-ofpocket expenses for medical and dental care and excluded premiums, over-thecounter drugs, and reimbursed costs.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility of underinsurance in the elderly population. To further support this, a study by Yala et al (24) showed that patients with diabetes receiving a low-income subsidy for Medicare Part D were found to have lower out-ofpocket (OOP) costs and better medication adherence, and those with private insurance with a deductible in the nonelderly population with diabetes are more likely to report forgoing needed medical services (25).…”
Section: Factors Associated With Crnmentioning
confidence: 99%